Provider Specific Nulliparous, Singleton, Vertex, Term Cesarean Rates Impact on Maternal and Neonatal Outcomes [33L]. (May 2020) - Fiori, Catherine; Altman, Alan; Marcotte, Michael Paul; Holbert, Michael
Abstract : INTRODUCTION: Recent national initiatives have proposed to reduce cesarean delivery rates. Institutions have reported increased neonatal and maternal morbidity secondary to these initiatives. This study evaluated the impact of provider level nulliparous, singleton, vertex, term cesarean section rates on maternal and neonatal outcomes for all laboring patients. METHODS: This was an IRB approved retrospective study of deliveries at a tertiary healthcare system over four years from January 1, 2015 to December 31, 2018. Nulliparous, singleton, vertex, term cesarean rates were calculated for each provider. Providers that were one standard deviation above and below the mean were grouped into high NSVT providers and low NSVT providers. All laboring patients of these two provider groups were then compared for maternal and neonatal outcomes. RESULTS: Of the 5465 deliveries, there were significant differences in cesarean section rates among high NSVT providers and low NSVT providers, 22.5% vs 6.0%, P<. 0001. High NSVT providers had higher rates of maternal fever, 6.1% vs 4.2% ( P= .0018 OR 1.47 CI 1.16-1.88), and maternal readmission, 1.6% vs 0.9% ( P= .0268 OR 1.73 CI 1.07-2.83). High NSVT providers had lower rates of 3rd or 4th degree lacerations, 1.6% vs 2.4% ( P= .0326 OR 0.65 CI 0.44-0.97), shoulder dystocia, 1.8% vs 2.6% ( P= .0289 OR 0.66 CI 0.46-0.96), and fetal macrosomia, 0.7% vs 1.3% ( P= .0250 OR 0.52 CI 0.29-0.92). All other measures were not significant. CONCLUSION: Providers with relatively high and low primary cesarean section rates exhibit different risk profiles for maternal and neonatal morbidity when examining all their laboring patients.